Subcontractor Standing and the Requirement of Creditor Plurality in Suspension of Debt Payment Obligations (PKPU) Proceedings: A Case Study of Decision No. 27/Pdt.Sus-PKPU/2024/PN.Niaga.Sby - Mohammad Ikhsan; Siti Anisah (Ilomata International Journal of Management, 2026)
This study examines the legal standing of subcontractors in Suspension of Debt Payment Obligations (PKPU) proceedings under Article 222 of Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Subcontractors often face legal vulnerability because they lack a direct contractual relationship with project owners despite fulfilling their contractual obligations. The central legal issue concerns whether subcontractors satisfy the creditor qualification required under Article 222 and thereby obtain legal protection in PKPU proceedings. This research employs normative legal methods using statutory, conceptual, and case approaches, focusing on Decision No. 27/Pdt.Sus-PKPU/2024/PN.Niaga.Sby. The analysis applies the doctrine of derdenbeding to assess the creation of enforceable rights for third parties within contractual arrangements, while John Rawls’s theory of justice evaluates whether judicial reasoning adequately protects economically vulnerable parties in construction disputes. The findings reveal that subcontractors may acquire creditor status when contractual structures and supplementary agreements expressly grant direct rights against project owners, thereby fulfilling the legal requirements for claim recognition in PKPU proceedings. The analyzed decision demonstrates that judicial recognition of creditor status depends not only on unpaid obligations but also on the existence of a legally enforceable relationship capable of generating a valid claim. This study contributes to insolvency and construction law scholarship by clarifying the doctrinal test for subcontractor standing in PKPU cases and demonstrating how derdenbeding clauses operationalize principles of fairness through judicial reasoning. Accordingly, PKPU functions as both a debt restructuring mechanism and a framework for balancing the interests of project owners, contractors, and subcontractors.